Translucency of Nanoparticles Reinforced Denture Base Materials - Ghadaq M. Younis; Radhwan H. Hasan (University of Mosul, College of Dentistry, 2024)
Aims: To evaluate the effect of adding salinized zirconium oxide (ZrO2) and silicon oxide (SiO2) nanoparticles in two concentrations on the translucency of heat-cured denture base material. Materials and methods: Fifty discs (15×2.5mm) were prepared in accordioning to the manufacturer's instructions and divided into five groups, control without nanoparticles reinforcement, 1%ZrO2, 3%ZrO2, 1%SiO2 and 3%SiO2 NPs reinforcement. Translucency was measured using a colorimeter. Results: The result showed a highly significant (P ≤ 0.01) decrease in the translucency ZrO2 Np reinforced more reduce in the translucency than SiO2 Np reinforced group. The 3% by weight is more reduced than 1% by weight. Conclusions: Both nanoparticles reduced the translucency.